How prophecy lives - Tumminia, Diana G.; Swatos, William H. (Religion and the Social Order, 2011)
Taking its inspiration from the 50th anniversary of the publication of Festinger and others's 1956 seminal and controversial volume When Prophecy Fails , which introduced the notion of \'cognitive dissonance\' as an explanation for how a small group of flying saucer devotees handled the failure of a predicted visit from space aliens, this volume looks at both theoretical and empirical studies of religious groups for whom space beings and civilizations provided an inspiration to prepare for the nearness of events that would trigger \'the end of the world.\' Rather than examining merely the rationales adopted to account for the disappointments associated with such \'failures,\' the core of the present volume seeks to explore the dynamics that inspire not only such beliefs but also the vigorous participation in activities in which adherents engage to prepare for the coming of (or transport to) alien civilizations from \'outer space.\'